Spontaneous Rhinorrhea mimicking sinusitis - (:unkn) unknown (AFRICAN FIELD EPIDEMIOLOGY NETWORK-AFENET, 2015)
Spotaneous or non-traumatic cerebrospinal fluid rhinorrhea is an uncommon condition and may present a diagnostic challenge to clinicians. This condition is often being misdiagnosed for allergic rhintis or chronic sinusitis since the precipitating cause is not readily apperent in most patients. The mechanism of rhinorrhea is stil not completely clarified. We describe a case of this condition occuring in association with allergic rhinitis and sinusitis. A 52 year-old, obese female patient presented with two weeks history of bilateral clear nasal discharge and postural headache. Sample of nasal discharge tested for glucose and protein. The result was that the collection fluid was cerebrospinal fluid. The origin of cerebrospinal fluid fistula could not be identified despite the diagnostic tests.
Keywords: Rhinorrhea; spontaneous rhinorrhea; sinusitis; CEREBROSPINAL-FLUID RHINORRHEA; SPONTANEOUS CSF RHINORRHEA